Management of mucinous cystic neoplasms of the pancreas - Testini, Mario (Baishideng Publishing Group Co., Limited, 2010)
The purpose of this study was to investigate the actual management of mucinous cystic neoplasm (MCN) of the pancreas. A systematic review was performed in December 2009 by consulting PubMed MEDLINE for publications and matching the key words “pancreatic mucinous cystic neoplasm”, “pancreatic mucinous cystic tumour”, “pancreatic mucinous cystic mass”, “pancreatic cyst”, and “pancreatic cystic neoplasm” to identify English language articles describing the diagnosis and treatment of the mucinous cystic neoplasm of the pancreas. In total, 16 322 references ranging from January 1969 to December 2009 were analysed and 77 articles were identified. No articles published before 1996 were selected because MCNs were not previously considered to be a completely autonomous disease. Definition, epidemiology, anatomopathological findings, clinical presentation, preoperative evaluation, treatment and prognosis were reviewed. MCNs are pancreatic mucin-producing cysts with a distinctive ovarian-type stroma localized in the body-tail of the gland and occurring in middle-aged females. The majority of MCNs are slow growing and asymptomatic. The prevalence of invasive carcinoma varies between 6% and 55%. Preoperative diagnosis depends on a combination of clinical features, tumor markers, computed tomography (CT), magnetic resonance imaging, endoscopic ultrasound with cyst fluid analysis, and positron emission tomography-CT. Surgery is indicated for all MCNs.